Case Report: Approach to Dog Bite Eyelid Injury in Rabies Endemic Area - Birapadian, SM; Ting, S L; Lim, C W (2021)
Sarawak has recorded 24 rabies cases, since an outbreak was declared on July 1, 2017. We are presenting a case report dis-cussing the approach to dog bite eyelid laceration in Rabies endemic area. A 13-year-old boy came with full-thickness lid lacera-tion wound, after being attacked by a stray dog. The patient received a dose of intramuscular anti-tetanus injection, followed by immunoglobulin injection at the laceration site, rabies vaccine as well as completed a course of antibiotics. The laceration was allowed for primary closure, and it healed well with adequate apposition. This paper we outlined the importance of immediate accurate risk category stratification for early identification of those at risk in the primary care setting help minimize the risk of rabies infection and save a life.